Edukasi Manfaat Akupresur untuk Meningkatkan Kualitas Tidur pada Masyarakat dengan Diabetes Melitus - Yessy Widhi Astuti; Fatimah Rahmawati; Alwan Dhafi Umar; Franciscus Xaverius; Retno Handayani; Siti Nur Rohmah (Universitas Pahlawan Tuanku Tambusai, 2026)
A decline in sleep quality is common among patients with diabetes mellitus and can interfere with physical and cognitive activities. Acupressure is a method with minimal side effects and is the easiest for people to perform on their own. Applying pressure to acupressure points accurately, gently, and slowly can modulate neurotransmitters to induce relaxation and improve sleep quality. This community service activity was conducted with the aim of improving the public’s knowledge and skills regarding acupressure to improve sleep quality in people with diabetes mellitus. The methods used included outreach, education, and demonstrations, with leaflets serving as teaching aids to facilitate understanding. The activity was attended by 31 participants. The results of the pre-test and post-test showed a shift in participants’ understanding levels: from “very poor” (19 participants) and “poor” (9 participants) to “good” (24 participants) and “very good” (2 participants). This indicates that effective education combined with hands-on demonstrations can improve knowledge of the benefits of acupressure and the skills needed to perform acupressure independently.